The Influence of Workload and Working Environment on Employee Performance with Motivation as an Intervening Variable in DM Baru 1 Pleret Bantul - Meivianti, Erlin; Wahyu Pratiwi, Krisnandini (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2025)
The purpose of this research is the examine the influence of workload and environment work on performance and through motivation as an intervening variable on DM Baru 1 Pleret Bantul employee. The phenomenon  in this research concerns performance employee at DM Baru 1 Pleret Bantul. The type of research carried out is quantitative or statistic research conducted to test hypothesis. Population in this research were all employee of DM Baru 1 Bantul. The technique saturated sampling or census taking is quantitative and is used to examine symptoms of group or individual behavior by distributing questionnaires. The analysis technique in this research uses descriptive analysis technique and quantitative analysis using SmartPLS 4.0 software. Result from research shows that Workload has a significant positive effect on Performance Employee. Work Environment has significant positive effect on Performance Employee. Workload has a significant positive effect on Performance Employee through Motivation as an intervening variable. The work Environment has a significant positive effect Performance Employee through Motivation as an intervening variable.